Evolution of Grade III Breast Cancers on the Portmann Scale - Valls, Alberto (Cirugía del Uruguay, 2020)
The course of mammary cancers grade III according to the Portmann scale seen at the University Hospital of the Medical School of Montevideo is surveyed.